Three-dimensional model for nonlinear analysis of slender flanged reinforced concrete walls. (1st June 2021) - Kolozvari, Kristijan; Kalbasi, Kamiar; Orakcal, Kutay; Wallace, John
Highlights: New, macroscopic, nonlinear, three-dimensional model for RC walls is proposed. Model is computationally stable and efficient, and publicly available in OpenSees. Results from multidirectional tests on non-rectangular walls used for validation. Analytically predicted load-deformation responses match well experimental data. Plane-sections assumption in the model affects accuracy of strain predictions. Abstract: A new, three-dimensional, four-node, macroscopic model element for nonlinear analysis of reinforced concrete walls is developed and implemented in the structural analysis software OpenSees. The two-dimensional, beam-column formulation of the Multiple-Vertical-Line-Element Model (MVLEM) is extended by implementing the geometrical transformation of the element degrees of freedom that convert the model element from a two-node to a four-node element, and by incorporating linear-elastic element out-of-plane behavior. The three-dimensional analytical model developed, namely the MVLEM-3D, is validated based on load-deformation responses and vertical strains obtained from tests on one T-shaped wall specimen tested under uniaxial cyclic loading and four U-shaped wall specimens tested under complex multidirectional loading protocols. In addition, results of sensitivity studies on model geometric discretization and selection of an effective shear stiffness are presented. The model exhibits a high level of numerical stability and computational efficiency for all specimens investigated. Comparisons of experimental and analytical results demonstrate that the proposed MVLEM-3D captures, with good accuracy, the cyclic load-displacement behavior of non-planar walls in loading directions that are parallel to the principal axes of the cross-section. However, the analysis results overestimate the wall lateral strength in diagonal (relative to the principal axes) loading directions by 20–50%. This discrepancy is associated with the inability of the plane-sections hypothesis implemented in the model to capture the experimentally-observed nonlinear strain distributions developing along the wall cross-section due to shear lag effect. Despite this issue, the proposed model is shown to be a powerful tool for practical applications, as nonlinear response history analysis is becoming more common in engineering practice.